2007
DOI: 10.1101/gad.1509007
|View full text |Cite
|
Sign up to set email alerts
|

A core transcriptional network for early mesoderm development in Drosophila melanogaster

Abstract: Embryogenesis is controlled by large gene-regulatory networks, which generate spatially and temporally refined patterns of gene expression. Here, we report the characteristics of the regulatory network orchestrating early mesodermal development in the fruitfly Drosophila, where the transcription factor Twist is both necessary and sufficient to drive development. Through the integration of chromatin immunoprecipitation followed by microarray analysis (ChIP-on-chip) experiments during discrete time periods with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
355
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(371 citation statements)
references
References 73 publications
15
355
0
1
Order By: Relevance
“…Context-specific binding might result from other TFs facilitating or inhibiting binding either directly or via changes to the chromatin structure and DNA accessibility (e.g., Zeitlinger et al 2003;Harbison et al 2004;Buck and Lieb 2006;Sandmann et al 2007;Heinz et al 2010;He et al 2011;John et al 2011;Kaplan et al 2011;Li et al 2011). Such a combinatorial model would be an elegant way to realize many gene regulatory states with a limited number of TFs and to achieve TF binding specificity within the context of a large genome.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Context-specific binding might result from other TFs facilitating or inhibiting binding either directly or via changes to the chromatin structure and DNA accessibility (e.g., Zeitlinger et al 2003;Harbison et al 2004;Buck and Lieb 2006;Sandmann et al 2007;Heinz et al 2010;He et al 2011;John et al 2011;Kaplan et al 2011;Li et al 2011). Such a combinatorial model would be an elegant way to realize many gene regulatory states with a limited number of TFs and to achieve TF binding specificity within the context of a large genome.…”
mentioning
confidence: 99%
“…However, the relation between TF motifs and in vivo binding sites is far from simple: First, there is typically a large discrepancy between the number of motif occurrences and in vivo binding sites and most of even the highestscoring motif occurrences are not bound. For example, during Drosophila embryogenesis, the mesodermal TF Twist binds to only about a thousand of the roughly 1 million Twist motifs in the genome (Sandmann et al 2007;Zeitlinger et al 2007;Zinzen et al 2009). Second, in vivo TF binding appears to be highly contextspecific, and the same TF typically binds to different genomic binding sites in different conditions (e.g., Zeitlinger et al 2003;Buck and Lieb 2006;Sandmann et al 2007;Zinzen et al 2009;Wilczynski and Furlong 2010;Palii et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All embryos were stained for Eve expression; arrows indicate Eve expression in the dorsal and cardiac mesoderm. Previous Twist ChIP-chip assays (Sandmann et al, 2007) identified a putative enhancer downstream of the C15 transcription unit (Fig. 4A, fragment 4; Fig.…”
Section: Fig 3 Overexpression Of Ladybird and C15 Represses Evementioning
confidence: 99%
“…In Drosophila, mesodermal expression of lbe and lbl is regulated by two enhancers, which were identified by ChIP-chip assays for the pan-mesodermal transcription factor Twist (Sandmann et al, 2007). One of the enhancers is located within the lbl intron (Fig.…”
Section: Research Articlementioning
confidence: 99%